PENGEMBANGAN INOVASI APLIKASI SISTEM INFORMASI PELAYANAN ELEKTRONIK DAN KAMTIBMAS AKURAT (SIPEKA) DI KABUPATEN INDRAGIRI HULU RIAU - Zella Septriadi; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
People who still stutter using technology so that there are still many who do not understand online service procedures through the application of electronic service information systems and accurate kamibmas (SIPEKA) ranging from the process of completing the registration biodata, the next process manually to complaints of incidents beyond the expectations of the community in Indragiri Hulu district so that the community still takes care of police documents manually. The purpose of this research is to find out the development of innovation through the application of Electronic Service Information System and Accurate Kamtibmas (SIPEKA) in indragiri hulu district. After knowing this, the personnel of human resources related in the field of police is expected to be able to develop service innovations in the police department of Indragiri Hulu district resort. The study uses the theory of innovationowens, steinhoff and stoner (2018) U.S.AHA developed the idea of innovation that can include the effort of organizational change in four dimensions namely personnel dimensions, structural dimensions, task dimensions, technological dimensions. This study uses qualitative method with phenomenological approach. Informants in this study are the chief of police indragiri hulu district, paur public relations along with the implementing staff of electronic service information system application and accurate kamtibmas (SIPEKA). The informant was taken using snowball sampling. Data collection is done by observation, interview, documentation and literature studies. Analyze data using linear and hierarchical approaches. Halis research shows that there is still a lack of approach to the people of indragiri hulu district both in terms of socialization to the community, the introduction of the benefits of service innovation, to coaching the community in using online service innovations based on smartphones.  Keyword : Keywords: Development, Service Innovation, Electronic Service Information System Application And Accurate Kamtibmas (SIPEKA).